Acute effect of vibration training with a portable muscle-tendon vibrator on muscle power - Luo, J.; McNamara, B.; Moran, K. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland), 2004)
Vibration training has gained in popularity in recent years as a method of enhancing strength training (Cardinale and Bosco, 2003). A portable muscle-tendon vibrator which can be strapped to muscle tendon during strength training exercise has been developed. The aim of this study was to investigate the acute neuromuscular response to a bout of vibration training using this muscle-tendon vibrator. The muscle-tendon vibrator developed in this study could stimulate muscle to exert greater power during strength training. More muscle fatigue was elicited by the strength training exercise with added vibration. There was a facilitatory effect on power performance immediately after vibration with no exercise.